Mutagenic effectiveness and efficiency of gamma rays and EMS in soybean (Glycine max (L.) Merrill) - Satpute, R A; Fultambkar, Rajendra V (Current Botany, 2012)
Mutagenic effectiveness and efficiency of EMS and gamma rays were studied in the two varieties of soybean (MAUS-71 and JS-335). Both mutagens produced high frequency as well as wide spectrum in mutation. The frequency of mutation was high at lower concentration % / dose of mutagen. The mutagenic effectiveness and efficiency was calculated based on biological damage. Mutagenic effectiveness and efficiency reduced with the increase in concentration / dose of mutagen. In present investigation EMS proved to be effective in two varieties and gamma rays proved to be more efficient.